Studi Kritis Pertimbangan Hakim Pengadilan Agama dalam Perkara Hak Asuh Anak - Suyinah; Nawa Angkasa; Azizah Aziz Rahmaningsih (Jurusan Hukum Acara Peradilan dan Kekeluargaan, 2025)
The family is the smallest unit in society and is not immune to internal conflicts, including divorce. Divorce often has a serious impact on the psychological and mental condition of children, leading to issues related to child custody. The Religious Court has the authority to resolve child custody disputes through decisions that take various aspects into consideration. This study aims to analyze the factors that influence judges' considerations in formulating decisions in child custody cases. Using a descriptive qualitative approach, this research examines a number of judicial decisions and objectively describes the underlying considerations. The findings indicate that judges’ considerations are not solely based on normative provisions, but also include psychological aspects, the child's well-being, trial evidence, and expert reports. Factors influencing the judges’ decisions include: the plaintiff’s dishonesty in providing truthful statements during the trial, the absence of supporting evidence for the plaintiff’s claims, and the judges’ assessment that the child's welfare is better secured with the defendant, thus leading to the rejection of the claims. In addition, the defendant’s health condition, ability to provide care and education, as well as an environment considered conducive to the child’s development, are key factors taken into account in formulating the decision.